The effectiveness of technology for programming learning with Android Based In UIN SU's Computer Science Study Program - Rakhmat Kurniawan Ramli; Ahmad Taufik Al Afkari Siahaan (SEAN Institute, 2023)
The popularity of Android devices and the availability of various educational applications will provide many benefits, this is because android supports various multimedia formats, allowing the integration of audio, video, and animation to improve the understanding of concepts and learning content on Android applications can be updated easily. As many as 99% of students and lecturers of UINSU's computer science faculty own android smartphones. Programming material is a complex learning material and difficult for students to understand in both theory and attraction transfer courses. Therefore, interesting learning media is needed to make it easier for students to understand the content of the learning material. The results of this research are the development process, feasibility and implementation results of android application-based programming learning.